Cellular automata models of tumour natural shrinkage - Naumov, Lev. (2013)
In this paper we present three dimensional cellular automata models for tumour growth, with a focus on the tumour’s natural shrinkage caused by the removal of the dead cells’ mortal remains. The significance of this phenomenon for the resulting volume of the in silico tumour is shown. Two algorithms are presented, one using the chain shifting approach for tumour expansion and shrinkage and another improving the performance of the chain shifting approach. Simulations are validated against the experimental results.